The Rights of Children from Illegal Marriages of Indonesian Migrant Workers (TKI) in Selangor, Malaysia: A Review from the Perspective of Child Protection Law - Zakirah Anshori, Qory; Lubis, Fauziah (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
The phenomenon of illegal marriages among Indonesian Migrant Workers (TKI) in Selangor, Malaysia, especially in the Gombak area, has raised serious legal and social issues, especially concerning the protection of children's rights. Marriages that are not officially registered (nikah siri) cause children from these relationships to face difficulties in obtaining identity documents, citizenship status, access to education, and other basic services. This situation reflects the gap between the legal protection guaranteed by Law No. 35 of 2014 concerning Child Protection and its implementation in the context of cross-jurisdictional countries. This study aims to analyze how the Child Protection Law is applied to children from illegal marriages of TKI abroad, with a focus on access to education and legal status. The method used is a juridical-empirical approach through descriptive qualitative research, with data collection through interviews, field observations, and document studies in the TKI community of SB Sungai Mulia, Gombak, Malaysia. The results of the study indicate that although Law No. 35 of 2014 provides a strong legal basis, its implementation abroad faces major obstacles, including the limitations of Indonesian legal jurisdiction, strict Malaysian regulations, and minimal administrative awareness of Indonesian migrant workers. Data from 2024 recorded that more than 5,400 children of Indonesian migrant workers in Selangor were born from unregistered marriages, with the majority not yet having citizenship status. The Indonesian government has sought solutions through the overseas marriage validation program, the issuance of Birth Registration Certificates (SPL), and the establishment of non-formal learning centers. However, structural obstacles and suboptimal bilateral policies still hinder the fulfillment of children's rights in full.